Real-Life Management of Elevated Troponin Level in Patients Treated with Immune Checkpoint Inhibitors - Lior Zornitzki, MD; Dana Viskin, MD; Ophir Freund, MD; Ido Wolf, MD; Anna Rozenfeld Hemed, MD; Noam Weiss, MS; Shir Frydman, MD, Ms; Maor Tzuberi, MS; Shafik Khoury, MD; Ofer Havakuk, MD; Yan Topilsky, MD; Shmuel Banai, MD; et al. (CJC Open)
Background: Immune checkpoint inhibitors (ICIs) have revolutionized the clinical outcomes of cancer. Nevertheless, their use may lead to myocardial injury. The 2022 European Society of Cardiology cardio-oncology guidelines recommend routine follow-up of troponin level; however, current guidelines do not provide specific protocols for managing elevated troponin levels during ICI therapy. We aimed to describe the real-life assessment of patients treated with ICIs, presenting with an elevated high-sensitivity troponin I (hs-TnI) level following therapy. Methods: Tel Aviv Sourasky Medical Center has implemented a routine follow-up of hs-TnI level measurement during ICI therapy. We performed a retrospective analysis evaluating the clinical assessment and management of patients presenting with an elevated hs-Tnl level (> 50 ng/L) following therapy. Results: Among 455 patients performing baseline and follow-up hs-TnI measurements, 50 patients (11%) presented with an elevated hs-TnI level (median 159 ng/L; interquartile range 76-362) following ICI therapy. All patients underwent an electrocardiogram, showing changes in 5 patients (10%). Among 24 patients (48%) who received echocardiography, 4 (8%) showed abnormalities. A cardiology consultation was ordered for 17 patients (34%), and none received cardiac magnetic resonance imaging or coronary angiography. A total of 13 patients (26%) were diagnosed with probable or possible myocarditis, resulting in corticosteroid therapy and discontinuation of ICI therapy in 84% and 92% of the patients, respectively. Only 2 patients reinitiated ICI therapy at a later stage. Conclusions: We describe for the first time the management of elevated hs-TnI levels following ICI therapy, which was diagnosed in routine serial surveillance. We found a wide diversity in management, low cardiology involvement, and high interruption of therapy, emphasizing the need for standardized protocol management guidelines. Résumé: Contexte: Les inhibiteurs du point de contrôle immunitaire (ICIs) ont révolutionné les résultats cliniques en cancérologie. Néanmoins, leur utilisation peut entraîner des lésions myocardiques. Les lignes directrices 2022 de la Société Européenne de Cardiologie portant sur la cardio-oncologie recommandent un suivi de routine de la troponine; cependant, les lignes directrices actuelles ne fournissent pas de protocoles spécifiques pour la gestion des niveaux élevés de troponine pendant le traitement par ICIs. Nous avons cherché à décrire l'évaluation en conditions réelles des patients traités par ICIs, présentant des niveaux élevés de troponine I à haute sensibilité (TnI-hs) suite au traitement. Méthodologie: Le centre médical Sourasky de Tel Aviv a mis en place un suivi de routine de la TnI-hs pendant le traitement par ICIs. Nous avons effectué une analyse rétrospective de l'évaluation clinique et de la prise en charge des patients présentant des taux élevés de TnI-hs (>50 ng/L) à la suite du traitement. Résultats: Parmi les 455 patients ayant effectué des mesures de la TnI-hs, de base et de suivi, 50 patients (11 %) ont présenté une TnI-hs élevée (médiane 159 ng/L ; écart interquartile [76-362]) à la suite d'un traitement par ICIs. Tous les patients ont subi un électrocardiogramme, montrant des changements chez 5 patients (10 %). Parmi les 24 patients (48 %) ayant subi une échocardiographie, 4 (8 %) ont montré des anomalies. Une consultation en cardiologie a été demandée pour 17 patients (34 %), et aucun n'a effectué d'imagerie par résonance magnétique cardiaque ou de coronarographie. Treize patients (26 %) ont reçu un diagnostic de myocardite probable ou possible, ce qui a entraîné une corticothérapie et l'interruption du traitement par ICIs chez 84 % et 92 % des patients, respectivement. Seuls deux patients ont repris le traitement par ICIs à un stade ultérieur. Conclusions: Nous décrivons pour la première fois la gestion des niveaux élevés de TnI-hs après un traitement par ICIs, suite à un diagnostic dans le cadre d'une surveillance sérielle de routine. Nous avons constaté une disparité marquée dans les méthodes de prise en charge, une faible implication des services de cardiologie et des interruptions fréquentes du traitement, ce qui souligne la nécessité d'établir des lignes directrices standardisées pour la gestion des protocoles.